GENETIC DETERMINATION OF THE MAIN COMPONENTS OF THE MEAN INTERANNUAL FLOW WADIS IN THE SEMI-ARID CLIMATE OF THE MAGHREB - M., Ladjel (university of eloued جامعة الوادي, 2020)
North of the Maghreb, the flow of the wadis is generated by the rains. The hydro-climatic network is not dense enough to reasonably estimate the flow in any watershed where the wadis are not gauged. There is a need to develop methods for the acceptable estimation of river flow. The average flow of wadis is conditioned by a combination of climatic factors and local physicogeographic and hydrogeological factors. The influence of these local factors is dominant on the small and medium watersheds through the subterranean supply, where the climatic factors determine the superficial flow. The mean interannual flow (MIF) is composed of a regional climatic flow and a potential local flow. Regional climate flow differs from the actual climate flow in a watershed. The objective of this research is the genetic determination of the main components of the average interannual flow of wadis in the semi-arid climate of the Maghreb.
artical
Keywords: flow, rain, climate, evapotranspiration, infiltration.